2022
DOI: 10.1002/jcla.24569
|View full text |Cite
|
Sign up to set email alerts
|

Potential of circulating lncRNA CASC2 as a biomarker in reflecting the inflammatory cytokines, multi‐organ dysfunction, disease severity, and mortality in sepsis patients

Abstract: Background: Long noncoding RNA (lncRNA) cancer susceptibility candidate gene 2 (CASC2) inhibits inflammation and multi-organ dysfunction in various ways. The present study was intended to explore the potency of blood lncRNA CASC2 as a biomarker for sepsis management.Methods: Totally, 184 sepsis patients and 30 healthy controls were enrolled. The reverse transcription-quantitative polymerase chain reaction was used to detect lncRNA CASC2 expression in peripheral blood mononuclear cell samples from the subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Some may roughly reflect the magnitude of the organ pathology—for example, liver injury (increasing transaminases levels), liver dysfunction (e.g., modestly increased bilirubin levels), liver failure (high bilirubin, profound coagulopathy), but there are, admittedly, many confounders. Human studies have demonstrated alterations in levels of numerous biomarkers in sepsis, and their correlation with organ failure and mortality, including markers of endothelial activation and injury, long noncoding RNAs, cancer protein biomarkers, and brain natriuretic peptide (64–68). Markers of leukocyte activation and function also associate with sepsis outcomes (67, 69–72).…”
Section: Resultsmentioning
confidence: 99%
“…Some may roughly reflect the magnitude of the organ pathology—for example, liver injury (increasing transaminases levels), liver dysfunction (e.g., modestly increased bilirubin levels), liver failure (high bilirubin, profound coagulopathy), but there are, admittedly, many confounders. Human studies have demonstrated alterations in levels of numerous biomarkers in sepsis, and their correlation with organ failure and mortality, including markers of endothelial activation and injury, long noncoding RNAs, cancer protein biomarkers, and brain natriuretic peptide (64–68). Markers of leukocyte activation and function also associate with sepsis outcomes (67, 69–72).…”
Section: Resultsmentioning
confidence: 99%
“…The long non-coding RNA cancer susceptibility candidate 2 (CASC2) is another lnRNA that has been demonstrated to regulate AQP1 expression in lung carcinoma epithelial cells and lung injury mouse models via the miR-144-3p/AQP1 axis [ 34 ]. In humans, CASC2 levels have been found to be decreased in septic patients compared to healthy individuals and could be utilized as a biomarker for disease severity and mortality [ 57 ].…”
Section: Aquaporin Long Non-coding Rnas and Micro Rnas In Clinical An...mentioning
confidence: 99%
“…LncRNA гена-кандидата 2 на восприимчивость к раку (cancer susceptibility candidate gene 2, CASC2) ингибирует воспаление и полиорганную дисфункцию. Экспрессия lncRNA CASC2 снижена у пациентов с сепсисом по сравнению с контрольной группой здоровых пациентов и у умерших от сепсиса по сравнению с выжившими [80].…”
Section: длинные некодирующие Rna (Lncrna)unclassified